Promoting Silk Fibroin Adhesion to Stainless Steel Surfaces by Interface Tailoring. Issue 2 (30th November 2022) - Emonson, Nicholas S.; Randall, James D.; Allardyce, Benjamin J.; Stanfield, Melissa K.; Dharmasiri, Bhagya; Stojcevski, Filip; Henderson, Luke C.
Abstract: Bonding dissimilar materials has been a persistent challenge for decades. This paper presents a method to modify a stainless steel surface (316 L), routinely used in medical applications to enable the significant adhesion of a biopolymer (silk fibroin). The metallic surface was first covalently grafting with polyacrylamide, to enable a hydrogen bonding compatible surface. The polymerisation was initiated via the irreversible electrochemical reduction of a 4‐nitrobenzene diazonium salt (20 mM), in the presence of an acrylamide monomer (1 M) at progressively faster scan rates (0.01 V/s to 1 V/s). Examination of the modified samples by FT‐IR was consistent with successful surface modification, via observations of the acrylamide carbonyl (1600–1650 cm −1 ) was observed, with more intense peaks correlating to slower scan rates. Similar observations were made with respect to increasing surface polarity, assessed by water contact angle. Reductions of >60° were observed for the grafted surfaces, relative to the unmodified control materials, indicating a surface able to undergo significant hydrogen bonding. The adhesion of silk to the metallic surface was quantified using a lap shear test, effectively using silk fibroin as an adhesive. Adhesion improvements of 5–7‐fold, from 4.1 MPa to 29.3 MPa per gram of silk fibroin, were observed for the treated samples, highlighting the beneficial effect of this surface treatment. The methods developed in this work can be transferred to any metallic (or conductive) surface and can be tailored to complement any desired interface. Abstract : The adhesion of silk fibroin to stainless steel was enhanced by electrografting polyacrylamide polymer on to the metallic surface. Adhesion of the silk fibroin to the stainless steel was evaluated using lap‐shear testing, with up to 7x improvement in ahdesion observed.